Assessment of Job Capacities of Young People with Mental Disabilities according to the Evaluation of Motor Skills - Baranauskienė, Ingrida; Radzevičienė, Liuda (Social Welfare: Interdisciplinary Approach, 2013)
Problem of employment talking about integration processes of people with disabilities in present economical situation is still unsolved. Changing labor market appreciates precise, productive and responsible workers. Employers look for employees who can easily deal with diffcult situations, be creative and innovative. This viewpoint concerns adults with disabilities, who have problems in fnding and keeping job after fnishing training in professional rehabilitation centers. The aim of this research is to identify motor functions needed for successful integration into the labor market. It was set up that motor performance in static lifting and static pulling corresponds to the requirements of professions that are taught in the rehabilitation centre for young people with mental disabilities.
Keywords: motor performance; motor functions; job requirements; people with mental disability